Kekerasan Fisik Yang Dilakukan Oleh Residivis Terhadap Anak Ditinjau Dari Undang-Undang Nomor 35 Tahun 2014 Tentang Perubahan Atas Undang-Undang Nomor 23 Tahun 2002 Tentang Perlindungan Anak - Cindy Febriana Pualam (Darma Cendika Catholic University, 2018)
Children, as apart of the young generation, are one of the potential human resources and the successor of the nation’s goals who hold strategic roles. Children’s teenager’s protection is an act or an effort consciously made by some parties for the security and welfare, and the fulfiiment of rights thant should be received and owned by the child, even before they were born. It is protected by the law. Children’s right and obligation has become the things that must be fullfilled and worth fighting for. There is a sentence in the Child Protection Law, in which consideration, that states every child has the right to live, grow, and thrive, and they have the right for protection from violence and discrimination as mandated in the Indonesian Constitution Year 1945. In relation to the constitution, special protection towards a child as a victim of violence is regulated in Article 68 Child Protection Law. Meanwhile, the restriction of violence towards children is regulated on Article 76C Child Protection Law. Next, recidivist is the repetition of similar criminal action by the same perpetrator who has been convicted in a certain period of time. It is regulated in Article 486,487 and 488, Criminal Code where there is a heavier criminal punishment for the crime included in the articles.